Correction of Turkish Characters with A Web-Based Semantic Method - Cakmak, Furkan; Diri, Banu (IEEE, 2015)
Correction of Turkish characters in a text, which written without using Turkish characters, takes quite time if done manually due to various constraints (keyboard keypad, editor restriction). In addition, it can be overlooked some words in many cases. Especially if the case is also a word of Turkish characterless (kir/kir) makes sense, it is quite natural to overlook them. In such cases, on the basis of word correction is inadequate, considering related word's place in the sentence, it is necessary to go to semantically corrections. Let's consider the following sentence kir dugunlerini cok severim. . Although kir is meaningful word, when the flow of sentences considered, kir must correct with kir. In this study, a semantic web based algorithm was designed and high success ratio was obtained, when correcting Turkish characters without using morphological tools.
Keywords: automatic correction of Turkish characters; web-based; natural language processing; deasciifier; Engineering; Telecommunications